2011
DOI: 10.1038/gene.2010.65
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the T-cell receptor alpha/delta locus and possible associations with multiple sclerosis

Abstract: A role for T cells in the pathogenesis of multiple sclerosis (MS) is well supported, evidenced by myriad immunological studies, as well as the unequivocal genetic influence of the major histocompatibility complex (MHC). Despite many attempts, no convincing genetic associations have been made between T-cell receptor (TCR) gene loci and MS. However, these studies may not be definitive because of small sample sizes and under-representative marker coverage of the chromosomal regions being investigated. To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…Previous studies using restriction fragment length polymorphisms (RFLP) as genetic markers have reported conflicting results regarding the influence of TCR gene polymorphisms on MS risk . A more recent study used single‐nucleotide polymorphism markers to revisit this and identified three potential loci of interest in TCR alpha V and constant gene regions …”
Section: Analyses Of Immune Repertoires In Msmentioning
confidence: 99%
“…Previous studies using restriction fragment length polymorphisms (RFLP) as genetic markers have reported conflicting results regarding the influence of TCR gene polymorphisms on MS risk . A more recent study used single‐nucleotide polymorphism markers to revisit this and identified three potential loci of interest in TCR alpha V and constant gene regions …”
Section: Analyses Of Immune Repertoires In Msmentioning
confidence: 99%
“…There are, however, linkages to TCR in human autoimmune diseases other than T1D. TCR genotype has been implicated in multiple sclerosis (MS) [25]. There are also well-documented associations of TCR genotype with other forms of autoimmunity including Sjogren's syndrome [26, 27] and narcolepsy [2830], which has a TCRA bias.…”
Section: The Tcr and “Missing Heritability”mentioning
confidence: 99%
“…TCR antigen recognition is dependent on the presentation of short antigen peptides by the major histocompatibility complex (MHC) proteins expressed on the surface of other cells. The direct molecular interaction between the peptides, i.e., the MHC complex and the TCR, greatly influences TCR gene usage and has a fundamental part in shaping T cell/expressed TCR repertoires, particularly during T cell maturation and differentiation [8]. TCR genes are located at three regions in the genome, 14q11.2 (TCR α, δ), 7q34 (TCR β) and 7p14 (TCR γ).…”
Section: Introductionmentioning
confidence: 99%